(untitled) (Research, Society and Development, 2024)
This work sought to explore the transformative force of maker culture at the State Technical School of Professional and Technological Education of Cuiabá-MT, aiming to innovate and modernize the teaching methodology in the classroom, in addition to making it more inclusive and collaborative in fields such as Computing, Workplace Safety and Sustainability. To this end, we seek a practical and collaborative approach, based on the maker culture, to employ the development and implementation of educational technological projects focused on the interests of students, as well as the areas of knowledge of the courses offered at the institution. We were able to observe the positive impact of maker culture on education, not only in terms of developing technical and innovative skills among students, but also in promoting social and environmental awareness. The new approach allowed us to develop and implement three significant projects that translate well into the effective integration of maker culture into teaching methodologies, in which students can apply theoretical knowledge in real-world situations, developing practical solutions to important problems and contributing to the safety and well-being of the community.